Thermal properties of Co/Au nanoalloys and comparison of different computer simulation techniques - Rapallo, A. (2012)
In this work we investigate the performance of several simulation techniques, i.e., Canonical Molecular Dynamics, Canonical Monte Carlo, and the Optimized Multicanonical Monte Carlo, to study melting-like transitions of Co/Au nanoalloys that are compared to those of pure Co and Au clusters of the same size. A surprising enhancement in the thermal stability of core/shell Co 13Au 42 is observed compared to both pure clusters of the same size and shape. The novel property is analyzed using energetic and vibrational contributions throughout a detailed microscopic dynamic analysis. © 2012 American Chemical Society.